On the computational fluid dynamics (CFD) analysis of the effect of jet nozzle angle on mixing time for various liquid heights - Bumrungthaichaichan Eakarach; Jaiklom Nattawat; Namkanisorn Apinan; Wattananusorn Santi (My University, 2016)
In the present work, the effect of nozzle angle (22.5º, 45º and 67.5º) on mixing time for jet mixing tanks with the various ratios of liquid height (H) to tank diameter (D), including 0.5, 1, and 1.5, are studied by using computational fluid dynamics (CFD). The results revealed that CFD model with standard k-epsilon is successfully employed to predict the concentration profiles and mixing time by using the fine mesh and second order upwind scheme. The simulated results showed that the different jet nozzle angles result in different flow patterns. The results also indicate that the mixing time is mainly a function of the jet potential core length. Moreover, the jet path length or jet centerline velocity (jet kinetic energy) is considered as the secondary effect on mixing time, which depends on the tank geometry. Key words: Computational fluid dynamics (CFD), jet, mixing, turbulence, k-epsilon model.
Keywords: Cyclone Separators and Fluid Dynamics